Activate software-based business model development tools: An exploratory study - Szopinski, Daniel

Digital Tools for Teaching Business Model Innovation in Information Systems: A newly developed didactic approach comprising video-based peer feedback - Szopinski, Daniel; John, Thomas; Kundisch, Dennis

Essays on Crowd Based Idea Evaluation - Empirical Evidence from an Anonymous Online Crowd - Görzen, Thomas

Intertwined Development of Business Model and Product Functions for Mobile Applications: A Twin Peak Feature Modeling Approach - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Software Business)
Mobile app stores like Apple's AppStore or Google's PlayStore are highly competitive markets for third-party developers wanting to develop successful applications. During the development process, many developers focus on the multitude of product functions but neglect the business model as an equally important part. As a result, developers often fail to meet customer needs, leading to unnecessary development costs and poor market penetration. This, in turn, raises the question of how we intertwine the business model and product functions during the development process to ensure a better alignment between the two. In this paper, we show this intertwined development by adapting the concept of Twin Peaks to the business model and product functions. Based on feature modeling as an abstraction layer, we introduce the concept of a Business Model Decision Line (BMDL) to structure the business model decisions and their relation to product functions structured in a Software Product Line (SPL). The basis of our feature models is the analysis of top listed applications in the app stores of Apple and Google. To create and modify both models, we provide an incremental feature structuring and iterative feature selection process. This combination of abstraction layer and development process supports third-party developers to build successful applications both from a business and a product perspective.
Keywords: Intertwined Development; Twin Peaks; Feature Model; Business Model; Product Functions

Conception of a digital Sales Bonus System based on Blockchain Technology - Rodehutskors, Luca Maurizio

Entwicklung eines Frameworks für Geschäftsmodelle im On-The-Fly Computing - Dirksen, Daniel

Kreativität in der Wirtschaftsinformatik: Ein systematischer Literaturüberblick von Experiment-Designs - Henke, Lena

Kreativitäts-Experimente in der Wirtschaftsinformatik - Ein systematischer Literaturüberblick - Recker, Davide Pietro

Eine semantische Analyse von Online-Bewertungen auf digitalen B2B-Märkten - Schulte, Tristan Aaron

Entwicklung eines Rahmenwerks zur Evaluation von Geschäftsmodellen zur Entscheidungsunterstützung für Kooperationen mit Startups am Beispiel der Schüco International KG - Golis, Miriam

Feasibility study on the use of Hypermedia/HATEOAS using an example of a RESTful API from the financial services environment based on OpenAPI/Swagger - Brockmeier, Felix Karl

Externe Stimuli zur Geschäftsmodell-Ideengenerierung: Ein Experimenteller Ansatz - Milder, Christoph

Conception of a digital Sales Bonus System based on Blockchain Technology - N., N.

Business model idea generation: An exploratory study on changing perspectives - Szopinski, Daniel; Kundisch, Dennis (2nd Business Model Conference)

How to teach business model innovation to 300+ students: An experience report - Szopinski, Daniel (2nd Business Model Conference)

Datengetriebene Geschäftsmodelle: Ein Literaturüberblick - Arendt, Lukas Sebastian

Extracting the Wisdom from the Crowd: A Comparison of Approaches to Aggregating Collective Intelligence - Görzen, Thomas; Laux, Florian (Tagungsband Multikonferenz Wirtschaftsinformatik 2018 (MKWI))

Design Options of Store-Oriented Software Ecosystems: An Investigation of Business Decisions - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Küster, Jochen; Kundisch, Dennis; Szopinski, Daniel (Proceeding of International Symposium on Business Modeling and Software Design)
Nowadays companies like Apple create ecosystems of third- party providers and users around their software platforms. Often online stores like Apple App Store are created to directly market third-party solutions. We call such ecosystems store-oriented software ecosystems. While the architecture of these ecosystems is mainly derived from busi- ness decisions of their owners, ecosystems with greatly different archi- tectural designs have been created. This diversity makes it challenging for future ecosystem providers to understand which architectural design is suitable to fulfill certain business decisions. In turn, opening a plat- form becomes risky while endangering intellectual property or scarifying quality of services. In this paper, we identify three main design options of store-oriented software ecosystems by classifying existing ecosystems based on similarities in their business decisions. We elaborate on the design options, discuss their main contributions, and provide exemplary ecosystems. Our work provides aspiring ecosystem providers with the reusable knowledge of existing ecosystems and helps them to take more informed architectural decisions and reduce risks in future.

Eignungsbewertung eines Enterprise Architecture Frameworks für das IT-Alignment zwischen Unternehmensstrategie und IT-Landschaft am Beispiel der Arvato SCM - Funke, Lars Christian

An Extended Perspective of Technology Pivots in Software Startups: Towards a Theoretical Model - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 39th International Conference on Information Systems (ICIS))